Firms' Wage Structures, Workers' Fairness Perceptions, Job Satisfaction and Turnover Intentions: Evidence from Linked Employer-Employee Data - Jens Mohrenweiser; Christian Pfeifer (Institute of Labor Economics (IZA), 2019)
The paper uses novel data for Germany linking worker and establishment surveys with administrative social security data for all workers in the surveyed establishments. From these data, four variables are generated that describe a firm's wage structure and the positions of workers within it: (a) workers' own absolute wages, (b) workers' conditional internal reference wages within firms, (c) the conditional wage dispersion in firms, and (d) workers' conditional external reference wages across firms. Three empirical contributions are made: (1) the impact of firms' wage structures on workers' perceived wage fairness as an important organizational justice variable, (2) the impact of firms' wage structures on workers' job satisfaction and turnover intentions, and (3) the contribution of the fairness considerations on the overall effects of the wage structure variables on workers' job satisfaction and turnover intentions. The findings suggest that equity and social status considerations as well as altruistic preferences towards co-workers and inequality aversion are important, whereas the evidence for signal considerations is limited.
Keywords: D63; I31; J28; J31; J63; M52; 330; income comparison; inequality; fairness; job satisfaction; turnover